Design and experimental evaluation of a light cut-off (baffle) plate for aftermarket LED motorcycle headlamps - Dwi Prasetyo; Elky Fakhriza; Beni Setya Nugraha (Journal of Automotive and Mechanical Applied Technology, 2025)
This study aims to determine the impact of replacing halogen lights with LED lights on two-wheeled vehicles, focusing on energy efficiency, light brightness levels, and operational temperatures of the lights to support road safety in areas with minimal road lighting, as well as on adjusting the light distribution of the applied LED lights. The method used was an experiment conducted on variables for which data were unavailable, necessitating manipulation of the research object. The experiment was conducted using a Honda Supra 125 FI motorcycle, with measurements of light intensity (lux), power consumption (watts), battery current (V), electric current (A), and operating temperature (°C). The known impact became a reference for regulating LED light distribution. The test shows that applying a barrier plate design to LED lights can provide focused lighting through its light distribution patterns. The application of the baffle plate design to LED lights provided focused lighting through its light distribution patterns. The use of LED lights provided a slightly higher intensity (6.4%) and an energy consumption efficiency 60% higher, with a reduction in operating temperature of 64%. The application results show that the light control plate successfully forms a bright-dark cut-off, with a uniform light distribution and consistent light intensity of 1854 lux. This indicates that the tested LED lamp maintains stable lighting performance without a decrease in brightness.